Modified March C - Algorithm for Embedded Memory Testing - Muddapu Parvathi; N. Vasantha; K.Satya Parasad (International Journal of Electrical and Computer Engineering (IJECE), 2012)
March algorithms are known for memory testing because March-based tests are all simple and possess good fault coverage hence they are the dominant test algorithms implemented in most modern memory BIST. The proposed march algorithm is modified march c- algorithm which uses concurrent technique. Using this modified march c- algorithm the complexity is reduced to 8n as well as the test time is reduced greatly. Because of concurrency in testing the sequences the test results were observed in less time than the traditional March tests. This technique is applied for a memory of size   256x8 and can be extended to any memory size.DOI:http://dx.doi.org/10.11591/ijece.v2i5.1587